2001
DOI: 10.1007/s004280100453
|View full text |Cite
|
Sign up to set email alerts
|

Gsα gene mutations in monostotic fibrous dysplasia of bone and fibrous dysplasia-like low-grade central osteosarcoma

Abstract: A series of nine cases with monostotic fibrous dysplasia (FD) and five cases of fibrous dysplasia-like low-grade central osteosarcoma (fd-like lgcOSA) were applied in a mutational analysis. Restriction digestion analysis, single-stranded conformational polymorphism (SSCP) analysis, and repeated sequencing demonstrated a R201H mutation in six cases and a R201C mutation in three cases of patients with monostotic FD. These results demonstrate that the presence of Gsalpha gene mutations is a constant finding in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 17 publications
2
39
1
1
Order By: Relevance
“…18,[35][36][37][38][39][40] Okada et al 41 studied eight cases of low-grade central osteosarcomas retrospectively and showed that proliferative cell activity evaluated by AgNOR and MIB-1 immunohistochemical staining was significantly higher in cases of low-grade central osteosarcoma than in fibrous dysplasia and might be helpful in differentiating low-grade central osteosarcoma from fibrous dysplasia. Pollandt et al 42 showed that Gsalpha gene mutations were a constant finding in cases of monostotic fibrous dysplasia. Nevertheless, they also reported a Gsalpha gene mutation in one of five cases of fibrous dysplasialike low-grade central osteosarcoma studied.…”
Section: Discussionmentioning
confidence: 99%
“…18,[35][36][37][38][39][40] Okada et al 41 studied eight cases of low-grade central osteosarcomas retrospectively and showed that proliferative cell activity evaluated by AgNOR and MIB-1 immunohistochemical staining was significantly higher in cases of low-grade central osteosarcoma than in fibrous dysplasia and might be helpful in differentiating low-grade central osteosarcoma from fibrous dysplasia. Pollandt et al 42 showed that Gsalpha gene mutations were a constant finding in cases of monostotic fibrous dysplasia. Nevertheless, they also reported a Gsalpha gene mutation in one of five cases of fibrous dysplasialike low-grade central osteosarcoma studied.…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiation affects 16-43% of parosteal osteosarcomas with the characteristic gene amplifications being retained and can be present at the first presentation (synchronous type) or at the time of recurrence (metachronous type). [7][8][9] Bone tumors analyzed previously for GNAS alterations include fibrous dysplasia (N = 405), [10][11][12][13][14][15][16] ossifying fibroma (N = 65), 10,12,[15][16] osteofibrous dysplasia (N = 19), 10,12-13 low-grade central osteosarcoma (N = 12) 10,13-14 , and parosteal osteosarcoma (N = 10). 10 GNAS mutations have been reported in fibrous dysplasia and have not been described until recently in any other fibrous osseous lesions with the exception of a single low-grade central osteosarcoma.…”
mentioning
confidence: 99%
“…10 GNAS mutations have been reported in fibrous dysplasia and have not been described until recently in any other fibrous osseous lesions with the exception of a single low-grade central osteosarcoma. 14 These reported GNAS mutations in fibrous dysplasia include p.R201C, 13 p.R201H, 13 p.R201S, 17 and p.Q227L. 13 A GNAS mutation in codon 201 (p.R201G) has been found in lesions in McCune-Albright syndrome.…”
mentioning
confidence: 99%
“…In addition, this method may not be readily adoptable in the differential diagnosis of parosteal osteosarcoma and benign processes, because myositis ossificans and other benign surface lesions unfortunately tend to show some proliferative activity, and their increased labeling indices may overlap with those of sarcoma. Pollandt and co-workers, 28 on the other hand, took a molecular approach by performing Gsa gene mutation analysis to separate low-grade central osteosarcoma and fibrous dysplasia. They found that all nine fibrous dysplasias harbored this mutation, whereas such abnormality was not identified in four of five examples of fibrous dysplasialike low-grade central osteosarcoma.…”
mentioning
confidence: 99%